(untitled) (AYUSHDHARA, 2024)
Arka Kalpana is nowadays a known Kalpana among the Ayurvedic procedures. It was introduced in Ayurvedic Pharmacy in the later part of the Samhita period, which is very specific in its mode of preparation and therapeutic effect. It is a more palatable form of Ayurvedic dosage forms in comparison to Swarasa (Juice), Kalka (paste), Kwath (decoction) etc. Arka Prakash is the first Ayurvedic classical text in which various kinds of distillation Procedures and heating methods are mentioned for preparing Arka from different types of Dravya for different diseases. In this context, Arka Kalpana is given specific importance and it opines that it has more potency in comparison to the other Kalpana. Today’s population is becoming more and more in demand for Arka Kalpana, which is the first choice because of its potency, lower dose, improved shelf life, ease of absorption, quick action, and patient compliance.